Effects of induction and inhibition of matrix cross-linking on remodeling of the aqueous outflow resistance by ocular trabecular meshwork cells - Yang, Yong-Feng (Sci Rep, 2016)
The trabecular meshwork (TM) tissue controls drainage of aqueous humor from the anterior chamber of the eye primarily by regulating extracellular matrix (ECM) remodeling by matrix metalloproteinases (MMPs). Glaucomatous TM tissue is stiffer than age-matched controls, which may be due to alterations in ECM cross-linking. In this study, we used genipin or beta-aminopropionitrile (BAPN) agents to induce or inhibit matrix cross-linking, respectively, to investigate the effects on outflow resistance and ECM remodeling. Treatment with BAPN increased outflow rates in perfused human and porcine anterior segments, whereas genipin reduced outflow. Using a fluorogenic peptide assay, MMP activity was increased with BAPN treatment, but reduced with genipin treatment. In genipin-treated TM cells, Western immunoblotting showed a reduction of active MMP2 and MMP14 species and the presence of TIMP2-MMP14 higher molecular weight complexes. BAPN treatment increased collagen type I mRNA and protein levels, but genipin reduced the levels of collagen type I, tenascin C, elastin and versican. CD44 and fibronectin levels were unaffected by either treatment. Collectively, our results show that matrix cross-linking has profound effects on outflow resistance and ECM composition and are consistent with the emerging paradigm that the stiffer the ECM, the lower the aqueous outflow facility through the TM.